2016
DOI: 10.1093/ecco-jcc/jjw184
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised, Double-blind, Placebo-controlled Trial ofTrichuris suisova in Active Crohn’s disease

Abstract: Background and Aims:To investigate the efficacy and safety of three different dosages of embryonated, viable eggs of Trichuris suis [TSO] versus placebo for induction of remission in mildly-to-moderately active ileocolonic, uncomplicated Crohn’s disease [CD].Methods:Adults with active CD [n = 252] randomly received six fortnightly doses of 250, 2500, or 7500 TSO/15 ml suspension/day [TSO 250, TSO 2500, TSO 7500], or 15 ml placebo solution/day, in a double-blind fashion, with 4 weeks’ follow-up. Primary endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 37 publications
0
69
0
8
Order By: Relevance
“…Pioneering clinical trials showed that treatments of helminth eggs or larvae provided some clinical improvement in patients with CD and ulcerative colitis with no AEs [4,14,15]. However, a recent phase 2, randomized, placebo-controlled, multicenter trial that tested Trichuris suis ova (TSO) in patients with active CD showed that TSO efficacy was not significantly superior to placebo [16]. In addition to testing helminths as an alternative therapy for intestinal diseases, helminth-derived anti-inflammatory mediators have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering clinical trials showed that treatments of helminth eggs or larvae provided some clinical improvement in patients with CD and ulcerative colitis with no AEs [4,14,15]. However, a recent phase 2, randomized, placebo-controlled, multicenter trial that tested Trichuris suis ova (TSO) in patients with active CD showed that TSO efficacy was not significantly superior to placebo [16]. In addition to testing helminths as an alternative therapy for intestinal diseases, helminth-derived anti-inflammatory mediators have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…These initial studies formed the basis of clinical trials treating patients with IBD or multiple sclerosis in the United States and Europe with TSO. However, to date, these trials have shown disappointing response rates and no significant reduction compared with placebo controls …”
Section: Reworming the Westmentioning
confidence: 99%
“…Image is adapted from Servier Medical ART response rates and no significant reduction compared with placebo controls. [83][84][85] Of most relevance to this review, studies using hookworm infection to treat asthma or TSO to treat allergic rhinitis patients have also been undertaken. However, no change in clinical measurements was seen in either study, 86 and although type 2 specific responses were detected against the hookworm, no regulatory immune responses were found.…”
Section: Re Worming the We S Tmentioning
confidence: 99%
“…bei den Eiern des Schweinepeitschenbandwurms ( Trichuris suis ovata ). Im Jahr 2011 noch als vielversprechende Therapiemöglichkeit aufgeführt, wurde diese Option nun aufgrund von 2 negativ ausgefallenen großen randomisiert-kontrollierten Studien - 1 aus Europa und 1 aus Nordamerika - zur Remissionsinduktion bei Morbus Crohn verworfen und wird als mögliche Therapie bei chronisch-entzündlichen Darmerkrankungen - und somit auch Colitis ulcerosa - generell nicht weiter verfolgt [6]. …”
Section: Tableunclassified